Akustyka, mimetyka, estetyka, artykulacja: Grecy o głoskach języka - Wolanin, Hubert (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The paper contains a thorough examination of the criteria used by the ancient Greeks for defining, describing and classifying the phones of the language. References are made to works by Plato and Aristotle, as well as to the text of the Techne grammatike attributed to Dionysius Thrax. In the dialogues of Plato, and especially in the Cratylus, one can find the first categorical characteristics of different groups of phones, formulated in acoustic terms, as well as individual descriptions of the mimetic qualities of particular phones, based on either sound effects or articulatory features. In Poetics, Aristotle defined the phone as such, connecting it with the notion of voice characterized by indivisibility, ability to create a complex voice (i.e. a word) and exclusively human origin. In setting out three main classes of phones, he based their definitional criteria on their articulatory features (the contact of speech organs or lack of it) on the one hand, and on their phonetic and acoustic properties (audible voice), i.e. on sound distinctness manifesting itself in acoustic autonomy on the other. In the Techne grammatike, in turn, particular classes of phones were identified and defined by formulating the conditions in which they produce voice characterized by a definite – high or law – aesthetic value. Despite the absence of an articulatory criterion, Greek grammarians succeeded in distinguishing all basic classes of phones, although they constantly looked at phones through the prism of letters, which led to them confusing the phonetic level with the graphic one, and thus made it impossible to create a conceptual and terminological apparatus which would be the means appropriate for identifying and describing correctly the whole stock of Greek phones.